Treating the burnt auricle using Biobrane. Issue 3 (1st December 2020) - Haines, Morgan; Allan, James; Wijewardana, Aruna; Cha, Jeon; Vandervord, John
Abstract : Auricle burns remain a challenge for surgeons who must navigate the common and morbid complication of chondritis through often complex and painful dressing regimes. Our technique involving the application of Biobrane promotes healing, is individualized, single application and conducive to topical antimicrobial application. We find it is a simple and effective approach to treating the burnt auricle.